IMPACT OF HEALTH FACILITIES AND LOW DEATH RATE OF COVID-19-IN GERMANY COMPARE TO OTHER EUROPEAN COUNTRIES - Firtz Bohmler; Dr. Faiz Muhammad Shaikh (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2020)
This research investigates the Impact of Health Facilities andlow death rate of COVID-19-in Germany compare to otherEuropean Countries. Data were collected from varioussecondary sources COVID-19 data base. According to resultsGerman health system with its up to 4 fold higher numberregional public hospitals and topic of many politicaldiscussions might have been one factor to keep mortalityrate -according to the given database- low. HoweverGerman doctors, without out any medicine like colleges allover the world were as helpless as everywhere.Oneessential fact according the statements of reputedvirologists might be an early discovery of Corona infectionby sincere attention, focussed testing and early start oftreatment. In Germany with its the easy access to healthservice in combination with the large number of hospitalsmight be the reason for the „lower“ death rate. Not toforget the tremendous engagement of highly qualifieddoctors and nurses who were willing and able to workbeyond imagination of a routine work.